Enrichment of Biscuits with Andaliman and Fermented Buffalo Milk Biscuits for the Intervention of Malnutrition in Children Under Five - Sembiring, Diana; Aritonang, Evawany Y.; Purba, Amir; Lubis, Rahayu (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Nutritional problems in children under 5 in Indonesia are very large and need effective intervention. Local ingredient is potential to create enrichment biscuits. AIM: This study aims to produce biscuits enriched with Andaliman (Zanthoxylum acanthopodium) and fermented buffalo milk and to perform organoleptic tests on the taste, color, aroma, and texture of the biscuits. METHODS: Three types of biscuits were made, namely, biscuits without Andaliman and fermented buffalo milk, biscuits with 2 g of Andaliman and 200 g of fermented buffalo milk, and biscuits with 3 g of Andaliman and 200 g of fermented buffalo milk. The all three biscuits were then tested organoleptically in the form of preferences by a panel of expert teachers to see choices for taste, color, aroma, and texture. The biscuits are then tested in a laboratory to assess their nutritional content. RESULTS: Biscuits with 2 g of Andaliman and 200 g of fermented buffalo milk had the greatest preference. Statistically, the three groups of biscuits differed in taste, aroma, and texture (p < 0.05). The nutritional content of biscuits is above the standards set by the Ministry of Health. CONCLUSION: Biscuits containing 2 g of Andaliman and 200 g of fermented buffalo milk have the potential to be produced as one of the intervention methods for under 5-year-old children malnutrition in Indonesia.